The Role of Multinational Corporations in Metropolitan Innovation Systems – Empirical Evidence from Europe and South-East Asia - Javier Revilla Diez; Martin Berger (European Regional Science Association (ERSA), 2004)
Using firm-level survey data from Barcelona, Stockholm, Vienna in Europe and Singapore, Penang (Malaysia) and Bangkok in South-East Asia the paper enquires into the different R&D and innovation behaviour of multinational and local companies in these Metropolitan Regions. Scrutinizing a set of input, throughput and output indicators as well as information on cooperation characteristics, we try to evaluate a) if the spatial pattern of more (intense) innovation activity in Europe when compared to South-East Asia is still valid; and b) if there are reasons to believe that R&D units of multinational corporations in Europe are mainly concerned with the enhancement of the knowledge base and the development of future competitiveness by tapping into localized knowledge and using the particular host regions' innovation systems, while, on the other hand, MNCs in South-East Asia use R&D to support existing production facilities in order to exploit an existing competitive advantage. We are able to show that there is still a major gap in the innovation performance between South-East Asia and Europe and that there are indeed indications that R&D units in Europe are more orientated towards the augmentation of the company's knowledge base.
Keywords: 330